Present and Future Application of Nanoparticle Based Therapies in B-Chronic Lymphocytic Leukemia (B-CLL) - Mansilla, Eduardo; Marin, Gustavo H.; Núñez, Luis; Larsen, Gustavo; Mezzaroba, Nelly; Macor, Paolo (IntechOpen, 2012)
None